The Measurement Of Good Corporate Governance In Islamic Banking And Its Effect On Financial Performance (Empirical Study Of Islamic Commercial Banks In Indonesia) - Rahdian, Alfiz; Mardian, Sepky; Razikun, Muhammad (SEKOLAH TINGGI EKONOMI ISLAM SEBI, 2023)
This research aims to measure the quality of Good Corporate Governance (GCG) in Islamic Banking and examine its effect on financial performance. The independent variables examined include GCG Index, Board of Commissioner (BOC), Audit Committee (AC), Sharia Supervisory Board (SSB), Gender Diversity of BOC and SSB. The dependent variable includes financial performance determined by Return on Assets (ROA). This research uses samples of 11 Islamic Commercial Banks period of 2015-2019. They were selected using judgement sampling method. The data analysis method used panel data regression analysis with Fixed Effect estimation model. The result revealed that the GCG quality of Islamic Commercial Banks in Indonesia adheres to 90% of the indicator used in the GCG Index. Despite that, the GCG Index found no significant effect on financial performance. Moreover, the Good Corporate Governance implication in Board of Commissioner, Audit Committee, Sharia Supervisory Board and Gender Diversity also found no significant effect on Islamic banking’s financial performance. Penelitian ini bertujuan untuk mengukur kualitas tata kelola bank syariah dan menguji dampaknya terhadap kinerja keuangannya. Variabel bebas menggunakan proksi dari indeks tata kelola, dewan komisioner, komite audit, dewan pengawas syariah, jender dewan direksi. Kinerja keuangan diukur dengan rasio ROA. Riset ini menggunakan 11 sampel bank syariah untuk periode 2015-2019. Sampel dipilih dengan pendekatan sampling judgement. Data dianalisis dengan regresi data panel dengan Fixed Effect sebagai model terpilihnya. Temuan riset menjelaskan bahwa tata kelola bank syariah sampel mencapai indeks sebesar 90%, namun tata kelola tersebut tidak berpengaruh signifikan atas kinerja bank syariah.